Clinical outcome and volumetric 3D analysis of biofluorescence imaging system guided surgery for Medication-Related Osteonecrosis of the Jaw(MRONJ) - Sooshin Hwang; Hyouk Keun Jee; Yesel Kim; Hong-Cheol Yoon; Pil-Young Yun; Jeong-Kui Ku (BMC Oral Health)
Abstract Background This study aims to evaluate the clinical outcome of biofluorescent imaging system (BIS) guided MRONJ surgery through analyzing 3D volumetric changes in CBCT data of bone structure. Methods BIS-guided surgery for MRONJ surgery was performed by grinding red-fluorescent area from remained residual bone detected by Qray-pen. CBCT data was collected preoperatively, postoperatively, and at last follow-up more than 3 months of each patient. Healing ratio per month was calculated through measuring difference between postoperative defect and last follow-up defect volume by analyzing CBCT. Results With mean follow-up period of 7.8 ± 4.8 months, twelve MRONJ surgeries of 11 patients (2 males, 9 females, mean 72.8 ± 13.7 years old) showed bone healing tendency without recurrence in average healing ratio of 5.49 ± 2.22% per month, with complete soft tissue closure. It was observed that the healing ratio per month did not show statistically significant differences based on location of MRONJ, size of post-operative defect volume, nor duration of bisphosphonate intake before surgery. Conclusions Based on three-dimensional bone analysis, efficacy of BIS-based MRONJ surgery was proved through the recovery pattern of underlying bone structure and no recurrence sign showing. Clinical trial registration Not applicable.